USE OF RECOMBINANT TUBERCULOUS ALLERGEN IN SCREENING FOR TUBERCULOUS INFECTION IN CHILDREN AND ADOLESCENTS - S. V. Zubareva; E. N. Turkin (Туберкулез и болезни лёгких)
Goal of the study: to define efficiency of tuberculous infection detection in children from 8 to 17 years old basing on the results of screening with recombinant tuberculous allergen skin test (RTA).Materials and methods. During 2015 in medical units of Kaliningrad Regions 24,483 children in the age from 8 to 17 years old (24.4% of all children of this age in KR) were screened for tuberculous infection with recombinant tuberculous allergen. The remaining children (69,366) were screened with Mantoux test.Screening results are the following: negative RTA result was in 23,565/24,483 (96.3%) persons, questionable – 382/24,483 (1.5%), positive – 536/24,483 (2.2%). The biggest number of questionable and positive results of RTA skin test was observed in children from 12 to 17 years old.Results of screening with Mantoux are the following: negative 9.5% (6,590/69,366) of those examined, questionable – 16.4% (11,376/69,366), positive – 74.1% (51,400/69,366).Introduction of screening with RTA in 24.7% of children in the age from 8 to 14 years old did not reduce the frequency of tuberculosis cases detection (0.016 and 0.015% out of those examined in 2015 and 2014) in Kalinigrad Region. In 2015 the detection rate was 3.5 fold higher in the districts where RTA screening had been introduced (0.35 and 0.10 per 1 000 examinations) And frequency of positive results as per Mantoux test and RTA tests differs to significant extend (72.7 and 2.2% respectively in children from 8 to 15 years old, and 78.4 and 2.1% in adolescents from 15 to 17 years old), thus reducing the post-screening examination load (reducing the number of those referred for additional examinations) when using RTA test for screening.